Internalisasi Nilai-Nilai Iman dalam Pendidikan Agama Islam: Telaah Al-Qur'an dan Hadis tentang Hakikat dan Tingkatan Keimanan - Kisti Wulan Dari; Nur Hidayah Adelia; Ranti Riani Nur Iffah; Zilvi Syalsabillah; Arin Setiani; Nadirah Syafitri; Alihan Satra (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
This study aims to analyze the concept of faith from the perspective of the Qur'an and Hadith and its relevance to the internalization of faith values ​​in Islamic Religious Education (PAI). This study is motivated by the importance of strengthening the aspect of faith as the foundation for character formation in students amidst various moral and social challenges. The method used is library research with a descriptive-analytical approach to verses from the Qur'an and Hadith related to the nature, levels, and implementation of faith. The results show that faith encompasses not only inner conviction but also is manifested through words and deeds. The Qur'an and Hadith explain that faith has levels that can increase or decrease according to the quality of one's obedience and good deeds. In the context of PAI, internalization of faith values ​​can be achieved through a learning process that emphasizes the cognitive, affective, and psychomotor aspects in an integrated manner. Thus, a comprehensive understanding of the nature and levels of faith contributes to developing students with Islamic character, noble morals, and spiritual steadfastness in everyday life